The Effectiveness of Project Online Collaboration Laboratory in Improving Science Process and Critical Thinking Skills - Juli Firmansyah; Widiasih Widiasih; Hendri Saputra; Dara Phon Kamilah; Verawati Ginting (FKIP Universitas Lampung, 2024)
This paper aims to determine the effectiveness of the implementation of the Project-based Collaboration (POC_Lab) online practicum model in improving students' Science Process Skills (SPS) and Critical Thinking Skills (CTS). This study uses a quasi-experimental method with a one-group pre-test and post-test design. The sample in this study was 50 students who had taken Basic Physics I and II courses. The research sample took part in the collaborative practicum with an online mode to complete physics project products in small groups. Students collaborated to apply fluid concepts to submarine and hydram pump products. Data were collected using KPS and CTS Test Questions, each with 4 essay questions given before and after the treatment. N_gain was used to determine the increase in students' KPS and ultimately determine the effectiveness of POC_Lab on students' KPS and CTS. The results showed that implementing POC Lab in project-based learning improved students' KPS and CTS. High effectiveness was seen in the increase in N-Gain in various aspects, especially in reasoning, argument analysis, hypotheses, and applying concepts. Keywords: science process skills, critical thinking skills, project-based physics practicum, collaborative online practicum.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp827-846